Gender Responsive Climate Smart Agriculture the Sub-Saharan African Approach - Gondwe, Therese; Huyer, Sophia; Zougmoré, Robert B.; Segnon, Alcade C; Dawit, Mahilet (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Sub-Saharan Africa is highly vulnerable to the impact of climate change resulting in significant crop productivity losses and increased workloads for women. Women and men are exposed to different climate shocks and experience different impacts based on gender-differentiated roles, rights and opportunities. Women and men are changing their cropping practices and this has different impacts on access to and control over income from crops Implementation of gender-sensitive Climate-smart agriculture (CSA) practices provide tangible benefits for farmers, especially women. Example od such benefits include; increased production and incomes and decreased workloads from the adoption of improved varieties, labour-reducing technologies and climate-smart production practices.